Peran Bumi Inpirasi Learning Center Dalam Mengedukasi Kesehatan Lingkungan Masyarakat - Suwanda Muflih Lukvianto; Dedi Herdiana (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2020)
BILC(Bumi Inspirasi Learning Center)  is an environmental-related institution. This research is to find out the problems, namely (1) How the Earth Inspiration program in educating environmental health (2) How the Earth Inspiration efforts in educating environmental health and (3) How are the results felt by the community with the Bumi Inspiration bank in educating environmental health.  This research is to find out the problems, namely (1) How is the BILC program in educating environmental health (2) How is BILC's effort in educating environmental health and (3) How are the results felt by the community with the presence of BILC in educating environmental health. The method used in this study is a qualitative method. From the results of the study found that; (1) BILC programs relating to environmental health, one of which is the waste bank. With the program carried out, namely the garbage bank, financial literacy and the Al- Qur'an Education.